Isolation, Identification and Antimicrobial Sensitivity Profiling of Escherichia coli and Salmonella Spp. from Dead Broiler in Local Market of Dhaka City - Islam, Khairul; Islam, Syidul; Khan, Roknuzzaman; Zabed, Akib; Khatun, Sharmin; Al-Maruf, Muhammad; Hossain, Mosharaf; Shiraj-Um-Mahmuda, Syeeda; Zahan, Afroj; Saiful Islam, K.B.M. (International Journal of Poultry Science, 2025)
Background and Objective: Broiler is an important meat type chicken in Bangladesh. Different bacterial infections affect broiler chicken farming and farmers use antibiotics to protect the birds, as a result antimicrobial resistance in broiler chicken increased day by day. This study was conducted to isolate E. coli and Salmonella spp. strains from broiler for assessing their susceptibility and resistance patterns to some selected antimicrobials. Materials and Methods: This study was carried out in Sher-e-Bangla Agricultural University, Dhaka for isolation, identification and antibiotic sensitivity profiling of Escherichia coli and Salmonella spp. from dead broiler in local market of Dhaka city. A total of 150 liver and heart samples were collected from dead broilers and cultured in different media for isolation of Escherichia coli and Salmonella spp. Confirmatory diagnosis is done by biochemical tests. Results: The prevalence of E. coli and Salmonella spp. in liver samples was 45.33% and 40% and in heart samples it was 44% and 38.67% respectively. The overall prevalence of E. coli and Salmonella spp. in broilers was 44.67% and 39.33%. Antibiotic sensitivity profiling of the isolated E. coli and Salmonella spp. was performed by the disc diffusion method against 10 commonly used antibiotics. The highest rate of sensitivity against E. coli was found with Ceftriaxone (52.24%) followed by Gentamicin (49.25%) and Streptomycin (44.78%). The highest rate of resistance was recorded in Tetracycline (52.24%) followed by Ampicillin (50.75%), Cefuroxime (47.76%), Amoxicillin (46.27%) and Co-Trimoxazole (46.27%). The highest rate of antibiotic sensitivity against Salmonella spp. was found with Ceftriaxone (52.54%) followed by Gentamicin (50.85%) and Streptomycin (47.46%). The highest rate of resistance of Salmonella was recorded in Cefuroxime (54.24%) followed by Ampicillin (52.54%), Cefixime (50.85%), Tetracycline (49.15%), Amoxicillin (47.46%) and Co-Trimoxazole (45.76%). Conclusion: Based on the present study, antimicrobial resistance against E. coli and Salmonella spp. increased day by day. From this study, it may be concluded that Ceftriaxone is highly sensitive to E. coli and Salmonella spp. which showed the best result followed by Gentamicin and Streptomycin in the present study.